Pengaruh Debt to Equity Ratio, Total Assets Turnover, Net Profit Margin, dan Firm Size Terhadap Kinerja Keuangan (Studi Empiris Perusahaan LQ45 Yang Terdaftar di BEI Periode 2019-2022) - Hutami, Tasyayu Kharisma; Nursiam (Jurnal EMT KITA, 2024)
This study aims to determine the influence of Debt to Equity Ratio, Total Assets Turnover, Net Profit Margin, and Firm Size on financial performance in LQ45 companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022. The research method used is quantitative research. The sampling technique was conducted using purposive sampling with a total of 79 samples. The data used in this study is secondary data obtained from financial statements on the IDX website (www.idx.ac.id) or the official website of each company. The data analysis method used is multiple regression analysis with the assistance of SPSS version 25. The research results indicate that the variables Total Assets Turnover, Net Profit Margin, and Firm Size significantly influence financial performance, whereas the Debt to Equity Ratio variable does not significantly affect financial performance.